A Case of Endoscopic and Surgical Treatment for Large Cell Neuroendocrine Carcinoma of the Lung with Endobronchial Growth - Kiriyama, Yosuke; Uomoto, Masashi; Hachisuka, Yasuki; Fujioka, Shinji (The Journal of the Japan Society for Respiratory Endoscopy, 2023)
Background. Performing surgery for a central airway tumor can require extensive invasiveness and substantial surgical stress. Case. A 67-year-old man was referred to our hospital for left-side pneumothorax and an evaluation of a right lower bronchial tumor on chest computed tomography. Bronchoscopy showed a tumor occluding the orifice of the right lower bronchus. A bronchoscopic biopsy was performed, and a pathological examination revealed large cell neuroendocrine carcinoma of the lung. The bronchoscopic findings showed a small nodule at the spur between the right middle bronchus and the right lower bronchus, but it was not deemed malignant by a frozen-section examination. We resected the tumor, which had extended to the truncus intermedius and occluded the orifice of the right lower lobe bronchus, using argon plasma coagulation with a flexible bronchoscope under general anesthesia. We further performed video-assisted thoracoscopic right lower lobectomy and lymph node dissection (ND2a-2). The resected bronchial stump was not malignant on a frozen-section examination. The postoperative progress was good, and the patient was discharged. Conclusion. By combining bronchoscopic and surgical treatment for tumors extending into the central bronchus, complete resection was possible under a minimally invasive approach.